Innovative Pedagogical Approaches in Physical Education: Enhancing Student Engagement and Motor Skills Development - Singh, Jaibir; Kaur, Rajwinder (Journal of Neonatal Surgery, 2025)
Physical education is transforming, with increasing emphasis on innovative pedagogical approaches to enhance student engagement and promote motor skills development. This paper explores the effectiveness of contemporary teaching strategies that move beyond traditional instruction, integrating technology, student-centered learning, and interdisciplinary methodologies. The study reviews evidence-based practices such as gamification, adaptive teaching models, cooperative learning, and experiential approaches that foster active participation and holistic growth. Additionally, the paper examines the role of digital tools, including augmented reality and wearable fitness devices, in creating immersive and data-driven learning environments. These innovations are complemented by strategies that prioritize inclusivity, psychological well-being, and personalized learning pathways, ensuring that students of diverse abilities and backgrounds can excel. The findings highlight the potential of reimagined physical education curricula to equip students with the skills and enthusiasm needed for active, healthy lifestyles in an increasingly dynamic world